A Laboratory-based Analysis of Nontuberculous Mycobacterial Lung Disease in Japan from 2012 to 2013 - Morimoto, Kozo; Hasegawa, Naoki; Izumi, Kiyohiko; Namkoong, Ho; Uchimura, Kazuhiro; Yoshiyama, Takashi; Hoshino, Yoshihiko; Kurashima, Atsuyuki; Sokunaga, Jun; Shibuya, Shunsuke; Shimojima, Masahiro; Ato, Manabu; et al. (Annals of the American Thoracic Society, 2017)
Since 2010, mycobacterial examination results have been used widely to survey nontuberculous mycobacteria (NTM) lung disease. To reveal the clinical and epidemiological status of NTM lung disease in Japan. All data on the isolation and identification of mycobacteria in 2012 and 2013 were obtained from three dominant commercial laboratories in Japan. Pulmonary NTM disease was defined on the basis of bacteriological diagnostic criteria issued by the American Thoracic Society/Infectious Diseases Society of America. The coverage population was estimated using the ratio between national tuberculosis registration data and laboratory results for each of the eight regions of Japan. A total of 113,313 mycobacterial specimens from 4,710 institutes were collected, and specimens from 26,059 patients tested positive for NTM cultures at least once. Among patients with positive cultures, 7,167 (27.5%) satisfied the American Thoracic Society/Infectious Diseases Society of America criteria for NTM lung disease, resulting in a 2-year prevalence rate of 24.0 per 100,000. Mycobacterium avium complex (MAC) was the most commonly isolated species (93.3%), and 29.0% of the patients from whom MAC was isolated satisfied the criteria for NTM lung disease. Individuals older than 70 years of age accounted for the majority of cases, and 65.5% of cases involved females. After MAC, Mycobacterium kansasii and Mycobacterium abscessus exhibited the highest (43.6%) and second-highest (37.1%) incidence per isolation, respectively. The prevalence of M. kansasii was highest in the Kinki region (P < 0.05), and M. abscessus had the greatest prevalence in the Kyushu-Okinawa region (P < 0.005). The proportion of Mycobacterium intracellulare in MAC cases was higher in the southwestern part of Japan than in other regions. The period prevalence was highest in the southwestern part of Japan, and the standardized prevalence ratio was highest in central regions. Evaluations of clarithromycin susceptibility revealed a clear binomial distribution. This investigation is the first laboratory-based study in which a large number of NTM isolated from clinical samples in Japan have been assessed. Although the calculated prevalence of NTM disease might be underestimated, the approach may prove useful for monitoring relative epidemiological data for NTM lung disease.